Polymorphisms of Catechol-O-Methyl Transferase (COMT) Gene in Vulnerability to Levodopa-Induced Dyskinesia - Ivanova, Svetlana A.; Alifirova, Valentina M.; Pozhidaev, Ivan V.; Freidin, Maxim B.; Zhukova, Irina A.; Osmanova, Diana Z.; Zhukova, Natalia G.; Mironova, Yulia A.; Tiguntsev, Vladimir V.; Fedorenko, Olga Yu.; et al. (Journal of Pharmacy & Pharmaceutical Sciences, 2018)
Purpose. Parkinson's disease (PD), a common neurodegenerative disorder, is usually treated with Levodopa (L-DOPA). The use of this drug, however, is severely limited by the development of side effects of the motor system: Levodopa-induced dyskinesia (LID). The aim of this study is to investigate the association between seven COMT gene single-nucleotide polymorphisms (SNPs) and the development of LID in patients with PD. Methods. 232 Caucasian patients with PD were investigated. 212 patients with PD received Levodopa therapy. Dyskinesia was assessed with the use of the Abnormal Involuntary Movement Scale (AIMS). Genotyping was carried out on seven SNPs of the COMT gene (rs4680, rs6269, rs4633, rs4818, rs769224, rs165774, rs174696) using a real-time PCR method, and blind to the clinical status of the subjects. Results. We found association between four SNPs, rs165774, rs4818, rs4633, rs4680, and LID. When the duration of disease was added as a covariate in regression analysis, however, the results did not reach statistical significance. Only the additive model for rs165774 was found to be close to be statistical significance (OR = 1.627 [0.976–2.741], permutation p = 0.057). Conclusions. The results failed to clearly support a contribution of the studied polymorphisms; this may be related to a dominant relationship with the disease duration confounding the effect on the prevalence of LID.